5GinFIRE continuous integration - Moreira, Sandra Inês Ferreira (2020)
With the current evolution of network connectable devices, traffic demands are becoming very high. Network operators need to ensure that they can provide new services faster but with the same quality while keeping the costs low. Given the traditional network architecture, that is not possible because the high demands require new hardware, and its substitution is costly and not flexible. By introducing the decoupling of network functions from traditional hardware, NFV is the technology that enables the step that network operators are trying to take. However, this approach also brings reliability concerns since it is mandatory to ensure that the virtual network functions (VNFs) behave as expected. 5GinFIRE is a project that aims to provide a 5G-NFV enabled experimental testbed. As this project handles multiple VNFs from the various experimenters, it is necessary to have an automated mechanism to validate VNFs. This dissertation provides a solution for the stated problem by having a system that verifies the syntax, semantics, and references of a VNF in an automated way without needing any further human interaction. As a result, a fully integrated testing platform is deployed in the 5GinFIRE infrastructure, and the results of the tests are issued in this Document.